THE COGNITIVE IMPACT OF 3D VISUALIZATION ON ABSTRACT MATHEMATICAL CONCEPT FORMATION IN SECONDARY EDUCATION - Alimov Bekzod Nematovich (Modern American Journals, 2025)
This article explores the cognitive impact of 3D visualization technologies on the formation of abstract mathematical concepts in secondary education, particularly within the context of the Uzbek educational system. The integration of 3D models and simulations into mathematics instruction represents a significant innovation in how abstract ideas such as geometric transformations, functions, and spatial reasoning are taught and internalized. By drawing on cognitive learning theories and recent developments in educational technology, the article evaluates the effectiveness of 3D visualization in enhancing conceptual understanding and reducing misconceptions among learners. The findings of the study are based on classroom observations, teacher interviews, and analysis of student performance before and after exposure to 3D content. The article concludes with recommendations for incorporating 3D visualization tools into pedagogical practices in mathematics education at the secondary school level.
Keywords: 3D visualization, cognitive development, mathematical abstraction, secondary education, spatial reasoning, geometry instruction, digital pedagogy, conceptual learning, interactive models, Uzbekistan education